A Study of Preferences for Sharing and Privacy - Olson, Judith S.; Grudin, Jonathan; Horvitz, Eric (2005)
We describe studies of preferences about information sharing aimed at identifying fundamental concerns with privacy and at understanding how people might abstract the details of sharing into higher-level classes of recipients and information that are treated similarly. Thirty people specified what information they are willing to share with whom. Although people vary in their overall level of comfort in sharing, we identified key classes of recipients and information. Such abstractions highlight the promise of developing expressive controls for sharing and privacy.